Labor Market in Postwar Bosnia and Herzegovina : How to Encourage Businesses to Create Jobs and Increase Worker Mobility - World Bank (Washington, DC, 2013)
Based on extensive institutional, and empirical analysis, the report describes a static labor market in Bosnia, unable to accommodate the economic imbalances resulting from the war, and from the legacy of the socialist era. Worker, and job flows have been rather low, lagging behind when compared with those in other transition economies. While the restrictive employment protection legislation - a strong barrier to labor mobility and job creation - was removed in the year 2000, replaced by a legislation attuned to the economy's needs, the highly structured wage system however, is still in place, precluding mobility, and job creation in the formal sector. The report identifies several findings, indicating the formal sector workforce practically denies access to young workers, reflecting a low labor force participation - where female labor force participation is among the lowest in the region - with large unemployment levels. Data emphasizes this point, showing a large informal sector, representing thirty six percent of total employment, and, the study presents evidence of under-reported wages to avoid, or minimize social security contributions. But despite the overall context of stagnant labor market, private firms have been much more dynamic in all aspects of job flows, including net employment growth. Newly privatized firms reduced their workforces, though not dramatically, which suggests no negative social impact of privatization have occurred to date. Recommendations include a strengthened business environment, within a comprehensive approach to social policy, reorienting active labor programs while continuing basic unemployment insurance.